The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/1350650115622366
|View full text |Cite
|
Sign up to set email alerts
|

Tribological effects of chlorine-free lubricant in strip drawing of advanced high strength steel

Abstract: This article investigated the tribological performance of the specially formulated chlorine-free lubricant in strip drawing of advanced high strength steel. Four different lubrication conditions (dry, chlorine-free lubricant, chlorine additive lubricant, and mineral base lubricant) at two sliding speeds (10 and 100 mm/min) were carried out to observe the friction coefficients of the die-workpiece interface in the strip drawing test. The main difference among these lubricants was the contents of chlorine and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…The countersamples were made from 1.2063 (145Cr6) tool steel. The strip test is a basic test for assessing friction conditions in sheet metal forming [39,40] The developed friction tester consisted of two rounded countersamples ( between which a strip of sheet metal with a width of w = 0.018 m moved durin The upper end of the sample was mounted in the holder of the Zwick/Roell Z1 machine. The normal force was set through a spring with known force-d characteristics (Figure 3).…”
Section: Friction Test Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The countersamples were made from 1.2063 (145Cr6) tool steel. The strip test is a basic test for assessing friction conditions in sheet metal forming [39,40] The developed friction tester consisted of two rounded countersamples ( between which a strip of sheet metal with a width of w = 0.018 m moved durin The upper end of the sample was mounted in the holder of the Zwick/Roell Z1 machine. The normal force was set through a spring with known force-d characteristics (Figure 3).…”
Section: Friction Test Proceduresmentioning
confidence: 99%
“…The countersamples were made from 1.2063 (145Cr6) tool steel. The strip drawing test is a basic test for assessing friction conditions in sheet metal forming [39,40].…”
Section: Friction Test Proceduresmentioning
confidence: 99%
“…Based on the values of the average friction force and the pulling force, the value of the coefficient of friction μ was determined from Eq. ( 1) (Jewvattanarak et al, 2016): Friction tests were carried out under lubrication conditions with hydraulic oil LHL32 (kinematic viscosity 21.9 mm 2 /s, density 874.1 kg/m 3 ), gear oil 75W-85 (kinematic viscosity 64.3 mm 2 /s, density 862.0 kg/m 3 ) and engine oil 10W-40 (kinematic viscosity 97 mm 2 /s, density 870.0 kg/m 3 ). Reference tests were performed for as-received surfaces of sheet metals.…”
Section: Friction Testmentioning
confidence: 99%
“…It was found, in general, that all the vegetable oils (i.e., linseed, rapeseed, sunflower, and palm) with the addition of boric acid were shown to be effective in lowering the COF. Jewvattanarak et al [24] used different lubrication conditions at two sliding speeds (10 and 100 mm/min) to determine the COF of a hot-rolled JSH780R steel sheet. The experimental results revealed that a mixture of chlorine and sulphur additives in the lubricant provided the best adsorption ability for the metal oxides.…”
Section: Introductionmentioning
confidence: 99%